2009
DOI: 10.1017/s0024282909008093
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation in the Lepraria isidiata-L. santosii group: a population study in the Mediterranean-Macaronesian region

Abstract: A thorough chemical, molecular and morphological study has been carried out on a problematic group in the genus Lepraria characterized by lobed, granular thalli with a raised rim and a preference for mosses, rocks and mineral soils in exposed, xeric habitats. The material examined was collected in seven countries of the Mediterranean-Macaronesian region, from chalk, carbonate rocks and derived soils (A-thalli), and from siliceous rocks and derived soils (B-thalli). The results of a phylogenetic analysis based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Since then, much attention has been paid to the taxonomy and chemistry of this group, and six species have been newly described, namely Orange and L. toensbergiana Bayerová & Kukwa (Tønsberg, 2002;Slavíková-Bayerová & Orange, 2006;Slavíková-Bayerová & Fehrer, 2007). However, the systematic position of the latter taxon has been briefly discussed (Bayerová & Haas, 2005;Baruffo et al, 2006;Fehrer et al, 2008;Tretiach et al, 2009;Saag et al, 2009), and a new combination L. jackii var. toensbergiana (Bayerová & Kukwa) Kukwa has been proposed (Śliwa & Kukwa, 2012).…”
Section: Lepraria Jackii Tønsberg Var Jackiimentioning
confidence: 99%
“…Since then, much attention has been paid to the taxonomy and chemistry of this group, and six species have been newly described, namely Orange and L. toensbergiana Bayerová & Kukwa (Tønsberg, 2002;Slavíková-Bayerová & Orange, 2006;Slavíková-Bayerová & Fehrer, 2007). However, the systematic position of the latter taxon has been briefly discussed (Bayerová & Haas, 2005;Baruffo et al, 2006;Fehrer et al, 2008;Tretiach et al, 2009;Saag et al, 2009), and a new combination L. jackii var. toensbergiana (Bayerová & Kukwa) Kukwa has been proposed (Śliwa & Kukwa, 2012).…”
Section: Lepraria Jackii Tønsberg Var Jackiimentioning
confidence: 99%
“…Chemical characters seem to be useful for the delimitation of species but do not reflect phylogenetic relationships within Lepraria (Ekman and Tønsberg 2002;Fehrer et al 2008;Nelsen and Gargas 2008). A species level study by Tretiach et al (2009), however, demonstrated considerable chemical variability within the two genetically and morphologically well-characterized species L. isidiata and L. santosii.…”
Section: Lecanoralesmentioning
confidence: 99%
“…is one of the few groups of lichenized fungi where there have been multiple attempts to use molecular phylogenetic analyses to confirm the monophyly of species delineated by nonmolecular characters (Slaví-ková-Bayerová and Fehrer 2007, Fehrer et al 2008, Tretiach et al 2009, Lendemer 2011a. Interestingly, these previous studies of have produced conflicting results regarding the utility of chemotaxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have supported the use of chemical characters to delineate species (Slavíková-Bayerová and Fehrer 2007, Fehrer et al 2008. Others, however, have recovered well-supported monophyletic entities that were chemically variable (Tretiach et al 2009). Based on these studies it is clear that within Lepraria s.l., chemical characters alone cannot a priori be used to circumscribe monophyletic taxonomic entities.…”
Section: Discussionmentioning
confidence: 99%